International transmission of inflation among G-7 countries: A data-determined VAR analysis - Yang, Jian; Guo, Hui; Wang, Zijun (Journal of Banking & Finance, 2006)
We investigate the international transmission of inflation among G-7 countries using data-determined vector autoregression analysis, as advocated by Swanson and Granger [Swanson, N., Granger, C., 1997. Impulse response functions based on a causal approach to residual orthogonalization in vector autoregressions. Journal of the American Statistical Association 92, 357–367]. Over the period 1973–2003, we find that unexpected changes in US inflation have large effects on inflation in other countries, although they are not always the dominant international factor. Similarly, shocks to some other countries also have a statistically and economically significant influence on US inflation. Moreover, our evidence indicates that US inflation has become less vulnerable to foreign shocks since the early 1990s, mainly because of the diminished influence from Germany and France.